Investigating the effects of a temperature dependent photodynamic dose: A numerical study - Andrew Effat; Nicholas Bernards; Runjie Bill Shi; Gang Zheng; Brian C. Wilson; Kazuhiro Yasufuku; Robert A. Weersink (Photodiagnosis and Photodynamic Therapy)
Significance: Photodynamic therapy (PDT) and photothermal therapy (PTT) show promise as cancer treatments, but challenges in generating large ablative volumes for deep-seated tumours persist. Using simulations, this study investigates combined PDT and PTT to increase treatment volumes, including the impact of a temperature-dependent PDT dose on the treatment volume radius. Approach: A finite-element model, using the open-source SfePy package, was developed to simulate combined interstitial photothermal and photodynamic treatments. Results compared an additive dose model to a temperature-dependent dose model with enhanced PDT dosimetry and examined typical clinical scenarios for possible synergistic effects. Results: Findings revealed that the temperature-dependent dose model could significantly expand the damage radius compared to the additive model, depending on the tissue and drug properties. Conclusions: Characterizing synergistic effects of PDT and PTT could enhance treatment planning. Future work is ongoing to implement additional variables, such as photosensitizer photobleaching, and spatial and temporally varying oxygenation.